Regional Growth Spillovers in Sub-Saharan Africa - Arizala, Francisco (IMF Working Papers; Working Paper ;, 2019)
This paper documents the steady increase in intraregional trade in sub-Saharan Africa since 1980, links this rise to important growth spillovers in the region, and identifies the main source countries and those most vulnerable to the economic conditions of others. Estimates show that in the short run, positive idiosyncratic shocks to regional trading partners' growth significantly increase growth in the average sub-Saharan African country, while in the long-run the annual impact of growth in regional trading partner's is smaller in magnitude. Policy implications including the need to support further continent-wide integration and the associated growth spillovers are discussed. Actions policymakers in sub-Saharan Africa can take to capture the benefits of these spillovers, while limiting exposure to the associated risks, are also proposed.